The utility of algae as sources of high value nutritional ingredients, particularly for alternative/complementary proteins to improve human health - Wu, Jia Yee; Tso, Rachel; Teo, Hwee Sze; Haldar, Sumanto (Frontiers in Nutrition, 2023)
As the global population continues to grow, the demand for dietary protein is rapidly increasing, necessitating the exploration of sustainable and nutritious protein sources. Algae has emerged as a promising food source due to their nutritional profile, containing high value ingredients, including proteins and for their environmental sustainability and abundance. However, knowledge gaps surrounding dietary recommendations and food applications restrict algae’s utilization as a viable protein source. This review aims to address these gaps by assessing the suitability of both microalgae and macroalgae as alternative/complementary protein sources and exploring their potential applications in food products. The first section examines the suitability of algae as a major food source by analyzing the composition and bioavailability of key components in algal biomass, including proteins, lipids, dietary fiber, and micronutrients. Secondly, the biological effects of algae, particularly their impact on metabolic health are investigated with an emphasis on available clinical evidence. While evidence reveals protective effects of algae on glucose and lipid homeostasis as well as anti-inflammatory properties, further research is required to understand longer-term impact of consuming algal protein, protein isolates, and concentrates on metabolic health, including protein metabolism. The review then explores the potential of algal proteins in food applications, including ways to overcome their sensory limitations, such as their dark pigmentation, taste, and odor, in order to improve consumer acceptance. To maximize algae's potential as a valuable protein source in the food sector, future research should prioritize on the production of more acceptable algal biomass for improved consumer acceptance. Overall, this paper supports the potential utility of algae as a sustainable and healthy ingredient source for widespread use in future food production.